Research on the excavation stability evaluation method of Chaqishan ancient landslide in China. (November 2022) - Wu, Lili; He, Keqiang; Guo, Lu; Zhang, Juan; Sun, Linna; Jia, Yuyue
Highlights: The excavation loading process of the slope was a one-way process of reducing stability, and the variety of excavation height was the main dynamic factor that led to the increase in the sliding force of slope. The evaluation model of the dynamic load-increasing displacement response ratio under the condition of slope excavation was established. The instability criterion of the excavation dynamic load-increasing displacement response ratio was established. The evaluation model of the excavation dynamic load-increasing displacement response ratio can be used to evaluate the stability in the process of slope excavation. Abstract: It is well known that the deformation and failure during the slope excavation often depends on the excavation height and slope rate. Based on the theory of loading and unloading response ratio, the present study established an evaluation model of the excavation dynamic load-increasing displacement response ratio and created the instability criterion. During the excavation, the stability law of the Chaqishan ancient landslide was analyzed using the Midas GTS NX finite element software, and four slope excavation schemes were redesigned. The results show that, the variation law of the excavation dynamic load-increasing displacement response ratio was consistent with the evolution law of stability coefficient, and there was an obvious negative correlation between them. Therefore, the stability variation law in the slope excavation could be evaluated using the evaluation model of excavation dynamic load-increasing displacement response ratio.